Cardiovascular risk in patients with coexisting Diabetes mellitus and Hypertension in Bang Chalong Health Promotion Hospital, Bang Phli District, Samutprakan Province - Chumpathat, Nopphanath; Chunchai, Siriporn; Wannaiampikul, Sivaporn; Akaratanapol, Prisana; Turongruang, Siriwan; Phuangprasonka, Rachada; Lee, Brian (Journal of Medicine and Health Sciences, 2022)
Abstract Diabetes mellitus and hypertension frequently occur together, which greatly increases the risk of cardiovascular disease. Diabetic patients with hypertension often have dyslipidemia and a waist circumference exceeding the norm. These abnormalities are components of a metabolic syndrome. The objectives of this study were to explore cardiovascular risk levels and associated factors in patients with concurrent Diabetes mellitus and hypertension without prior cardiovascular disease. The collected data from subjects who attended their annual health check-up at Bang Chalong Subdistrict Health Promotion Hospital, Bang Phli District in Samutprakarn Province. The cardiovascular risk level was determined by the Thai CV Risk Score. The results found that there were 190 eligible patients, 127 patients were females (66.8%), and 65.8% of all patients were aged 60 years old or over. The male patients who smoked had low levels of high-density lipoprotein cholesterol at a significantly higher proportion than female patients. Furthermore, 39.4% of patients with coexisting Diabetes mellitus and hypertension had a cardiovascular risk level > 20% or higher, and 79.5% had a metabolic syndrome. In addition, men were found to have a higher level of cardiovascular risk than women (OR=2.23, 95%CI=1.2-4.1, p=0.016), and patients aged 60 years old or over had a higher level of cardiovascular risk than those under 60 years old (OR=12.12, 95%CI=4.9-30.1, p<0.001). In conclusion, this study found more than one third of patients with concurrent diabetes mellitus and hypertension had higher cardiovascular risk levels. In particular, cardiovascular risk was significantly increased among elderly men.